Different composition of intraocular immune mediators in Posner-Schlossman-Syndrome and Fuchs’ Uveitis - Pohlmann, Dominika (PLoS One, 2018)
Posner-Schlossman-Syndrome (PSS) is clinically characterized by acute, recurrent, mild, unilateral uveitis anterior accompanied by elevated intraocular pressure (IOP). Fuchs´ Uveitis (FU) is a chronic, low-grade-inflammatory disorder, involving anterior uvea and vitreous. The clinical findings show remarkable similarities as well as differences. In our study, we determine the composition of immune mediators in aqueous humor of patients with PSS and FU and evaluate if immune mediators play a crucial role in specific viral intraocular inflammation and IOP rises. Aqueous humor samples from 81 uveitis patients (= eyes) presenting with either PSS or FU were collected at one time point. Local intraocular antibody synthesis to rubella virus was confirmed in 65 patients, whereas 16 were tested positively for human cytomegalovirus. Thirteen patients with PSS and 10 patients with FU were treated with glaucoma medications. Additionally, 11 cataract patients acted as control group. Immune mediator concentrations were measured by Bio-Plex Pro assay. We observed in both PSS (IFN-γ: 174.9 pg/mL; TNF-α: 25.1 pg/mL) and FU (IFN-γ: 25.4 pg/mL; TNF-α: 27.2 pg/mL) groups a significantly increased level of T-helper 1 immune mediators compared to controls (IFN-γ, TNF-α: 0 pg/mL) [median]. Notably, PSS patients (IL-1RA: 73.4 pg/mL; IL-8: 199.4 pg/mL; IL-10: 33.4 pg/mL; IP-10: 126350 pg/mL) showed a stronger and more active ocular inflammatory response, than FU patients (IL-1RA: 4.3 pg/mL; IL-8: 72.4 pg/mL; IL-10: 1.6 pg/mL; IP-10: 57400 pg/mL). Furthermore, a negative correlation between mediators and IOP was seen in the PSS group, potentially caused by acetazolamide-treatment. Our findings show that immune mediators play a crucial role in specific viral intraocular inflammation and influence IOP levels. Remarkable similarities but also significant differences of immune mediator concentrations are apparent in PSS compared to FU. High concentrations of IL-1RA, IL-8, IL-10, and IP-10 correlate with active inflammation in PSS, while FU may trigger chronic inflammation. Our data also substantiated a very similar composition of cytokines in those patients from the PSS group suffering from ocular hypertension and thus offers a potential explanation model for a negative correlation between mediators and IOP.